Dinamika Pertumbuhan Ekonomi di Provinsi Banten: Analisis Data Triwulanan 2018-2022 - Gentar, Muhamad; Permatasari, Intan; Kautsar, Wildan (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
This research aims to examine the dynamics of economic growth in Banten Province in the period of 2020-2023, using quarterly data obtained from the Economic Report of Banten Province published by Bank Indonesia. This research uses a descriptive-analytical method with a quantitative approach. The variables used are economic growth, inflation, banking intermediation, and regional budget expenditure. The results show that economic growth in Banten province tends to increase and is higher than national and regional economic growth in Java, although it is still influenced by factors such as inflation, banking intermediation, and regional budget expenditure. This research contributes to the development of the economy in Indonesia, especially in Banten province.